2018
DOI: 10.1155/2018/2086861
|View full text |Cite
|
Sign up to set email alerts
|

46,XY Disorder of Sex Development Caused by 17α-Hydroxylase/17,20-Lyase Deficiency due to Homozygous Mutation ofCYP17A1Gene: Consequences of Late Diagnosis

Abstract: Context Congenital adrenal hyperplasia (CAH) is an autosomal recessive disease due to specific enzyme deficiencies in the adrenal steroidogenesis pathway. Case Description A 40-year-old Chinese woman was referred to the Endocrine Unit for the work-up of a syndrome characterized by long-lasting and multidrug resistant high blood pressure, severe hypokalemia with metabolic alkalosis, and primary amenorrhea. The patient presented with sexual infantilism, lack of breast development, absence of axillary and pubic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…46,XY DSD patients with comorbidities of hypertension and hypokalemia may have mutations in the CYP17A1 gene, 29 and hence were excluded from our study. However, we found three patients with CYP17A1 gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…46,XY DSD patients with comorbidities of hypertension and hypokalemia may have mutations in the CYP17A1 gene, 29 and hence were excluded from our study. However, we found three patients with CYP17A1 gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, protein structure analysis has been done to examine the impact of specific mutants on a form of CAH known as salt-water wasting disease, which if left undiagnosed leads to low sodium levels and death (Haider et al, 2013). CYP17A1 is heavily involved in steroidogenesis, with deletion mutations leading to hormone production inhibition and sex development abnormalities (Keskin et al, 2015;Turkkahraman et al, 2015;Zhang et al, 2015;Papi et al, 2018;Xia et al, 2021). Recent genome studies of 17OHD patients revealed 46,XY karyotype in physically presenting females which cooccur with multiple mutations in the CYP17A1 gene (Zhang et al, 2015;Xia et al, 2021).…”
Section: Investigation Of Outlier Genes Associated With Genital Morphologymentioning
confidence: 99%
“…Additionally, protein structure analysis has been done to examine the impact of specific mutants on a form of CAH known as the salt‐water wasting disease, which if left undiagnosed leads to low sodium levels and death (Haider et al, 2013 ). CYP17A1 is heavily involved in steroidogenesis, with deletion mutations leading to hormone production inhibition and sex development abnormalities (Keskin et al, 2015 ; Papi et al, 2018 ; Turkkahraman et al, 2015 ; Xia et al, 2021 ; Zhang et al, 2015 ). Recent genome studies of 17OHD patients revealed 46,XY karyotypes in physically presenting females which co‐occur with multiple mutations in the CYP17A1 gene (Xia et al, 2021 ; Zhang et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a histogram of the results from 100 permutations where the mean difference was recalculated using the same number of randomly selected genes as the candidate genital genes is shown. deletion mutations leading to hormone production inhibition and sex development abnormalities (Keskin et al, 2015;Papi et al, 2018;Turkkahraman et al, 2015;Xia et al, 2021;Zhang et al, 2015). Recent genome studies of 17OHD patients revealed 46,XY karyotypes in physically presenting females which co-occur with multiple mutations in the CYP17A1 gene (Xia et al, 2021;Zhang et al, 2015).…”
Section: Investigation Of Outlier Genes Associated With Genital Morph...mentioning
confidence: 99%